Impact of Stress, Anxiety, Physical Tension, and the Perception of Vocal Handicap in Patients with Acquired and Congenital Vocal Lesions - Español, Español; Gassull, Cecilia; Casanova, Cori (Revista de Investigación en Logopedia, 2026)
This study aims to explore the relationship between the perception of vocal handicap, experiences of stress, anxiety, and bodily tension in contexts of high emotional demand or stress, as well as to analyze differences in these parameters between patients with acquired vocal fold lesions (AVFL) and congenital vocal fold lesions (CVFL). A sample of 201 patients was analyzed, each undergoing a differential diagnosis using videolaryngostroboscopy. Additionally, the Voice Handicap Index-10 (VHI-10) was administered to assess the perception of vocal handicap, along with an ad hoc questionnaire designed to evaluate experiences of anxiety, stress, and bodily tension in different parts of the body. A strong and significant correlation was identified between stress, anxiety, and various bodily tension variables. The results revealed significant differences between AVFL and CVFL patients in their experiences of anxiety and certain areas of bodily tension, particularly in regions related to vocal production. AVFL patients reported greater tension in the jaw, neck, and cervical areas, as well as a higher overall perception of bodily tension. Conversely, CVFL patients scored higher on the VHI-10, reflecting a greater perceived vocal handicap. These findings highlight the need for differentiated therapeutic approaches based on the type of dysphonia. They also emphasize the importance of addressing both physical and psychological aspects in the clinical management of these patients to improve their quality of life and therapeutic outcomes.